2000
DOI: 10.1518/001872000779656471
|View full text |Cite
|
Sign up to set email alerts
|

Putting It All Together: Improving Display Integration in Ecological Displays

Abstract: Computer displays are being designed for increasingly larger industrial systems. As the application domain scales up, maintaining integration across different kinds of views becomes more challenging. This paper presents the results of a study of three different approaches to integration based on the spatial and temporal proximity of related information objects. The domain used for evaluation was a simulation of an industry-scale conventional power plant. All three displays were ecological displays developed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 15 publications
4
61
0
3
Order By: Relevance
“…Their experience varied from working in Air Tra c Control (ATC) and ATM domains to aircraft control systems. Several studies investigating EID and sensor failure detection have shown that making the relationships between functional constraints and interface objects more explicit will improve fault diagnosis (see Burns (2000); St-Cyr et al (2013)). In this context, making the relationships between the conflict zones in the SSD and the aircraft on the PVD more explicit should expedite fault diagnosis.…”
Section: Participants and Tasksmentioning
confidence: 99%
See 1 more Smart Citation
“…Their experience varied from working in Air Tra c Control (ATC) and ATM domains to aircraft control systems. Several studies investigating EID and sensor failure detection have shown that making the relationships between functional constraints and interface objects more explicit will improve fault diagnosis (see Burns (2000); St-Cyr et al (2013)). In this context, making the relationships between the conflict zones in the SSD and the aircraft on the PVD more explicit should expedite fault diagnosis.…”
Section: Participants and Tasksmentioning
confidence: 99%
“…We hypothesize that presenting these links will expedite fault diagnosis and monitor automation decisions to pending separation conflicts. Note that the topic of EID and sensor failure, and the explicit representation of relationships between display features, has been studied before in process control (e.g., St-Cyr et al (2013); Burns (2000)), but not yet in the context of aviation featuring fast dynamics and short time constants. This paper is structured as follows.…”
Section: Introductionmentioning
confidence: 99%
“…Abstract functions are the work domain's underlying flows and causal relationships. Although a power plant (Burns, 2000), pasteurizer (Reising, 2002), and car (Burns & Hajdukiewicz, 2004) have different functional purposes, they can all be described fundamentally as flows of mass and energy governed by the laws of thermodynamics. As an information processing system, a decision aid can be described fundamentally as flows of information that may be governed by mathematical theories.…”
Section: Abstraction Hierarchymentioning
confidence: 99%
“…Burns research has shown that high-time and high-space (or integrated view visualization) supports performance better than multiple-view visualizations presented either simultaneously or sequentially (Burns, 2000). She argues that the reason for this is that integrated-view visualizations are able to show the data in a meaningful way.…”
Section: Abstract Data Verse Domain Specific Datamentioning
confidence: 99%
“…The research literature presents two opposite lines of thought regarding multiple-view versus integrated-view visualization. On one hand, some authors emphasize the advantages of layering information and integrating more information in one view (Burns, 2000;Tufte, 1983). On the other side, different authors argue for the advantages of splitting information into multiple-views (Roberts, 1998).…”
Section: Introductionmentioning
confidence: 99%